Analisis Pengendalian Persediaan Bahan Baku Food & Baverage Pada Hotel Grand Diamond Dengan Pendekatan Model Economic Order Quantity (EOQ) - Adelia Maulida Putri (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Raw material inventory control is a crucial aspect of a hotel's Food & Beverage (F&B) operations, ensuring smooth service and preventing stockouts. This study aims to analyze F&B raw material inventory control at Grand Diamond Hotel Yogyakarta using the Economic Order Quantity (EOQ), Safety Stock, and Reorder Point (ROP) methods. Employing quantitative descriptive approach, the study analyzes usage and ordering  for five key raw materials cooking oil, chicken and beef sausages, UHT milk, large format (gallon) mineral water, and rice on period  from July to October 2025. The results indicate a monthly increase in raw material usage. Cooking oil recorded the highest consumption at 1,376 liters, followed by sausages (1,144 packs), milk (1,054 liters), mineral water (646 gallons), and rice (1,050 kg). Implementing the EOQ method resulted in more optimal order quantities compared to hotel's conventional system, leading to more controlled and efficient inventory management. Furthermore, Safety Stock calculations successfully provided a buffer against demand uncertainty, while the ROP helped determine the precise timing for reordering. The application of EOQ, Safety Stock, and ROP methods proved more effective in enhancing inventory control efficiency, maintaining raw material availability,and supporting the smooth operation of the F&B department at Grand Diamond Hotel Yogyakarta.